1995
DOI: 10.1111/j.1365-2621.1995.tb06283.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity and Heat Lability of Antigenic Determinants of Duck and Goose Lysozymes

Abstract: Two panels of monoclonal antibodies (Mabs) raised against duck (Barbary) egg white lysozyme or hen egg white lysozyme, were tested in antigen-coated plate (ACP) and double antibody sandwich (DAS) ELISA for cross-reaction with various avian lysozymes. The antibodies to hen lysozyme cross-reacted with goose lysozyme, but most antibodies to duck lysozyme reacted with it. One antibody to duck lysozyme reacted more strongly with goose lysozyme than with the homologous antigen, a heterospecific reaction confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…On the other hand, it was also observed, that neither the electrophoretic behavior nor peak intensity of this protein changed using middle to low temperatures from 25 to 807C, the latter corresponding to the maximum temperature typically used for pasteurization. Although it has been shown that the dissolution pH has some effect on the thermal denaturation of egg-white proteins [71], our results indicate that the procedure based on CE-MS can be less influenced by thermal degradation than those procedures based on antigen-antibody reactions [69,70,72]. Moreover, although the sensitivity provided by immunodiagnostic techniques is in general better than those one obtained by CE-MS, some other aspects, like the longer analysis times usually required for these immunotests (typically hours for ELISA vs. 30 min for CE-MS) and the risk of obtaining false positives due to cross reactions, have also to be kept in mind.…”
Section: Ce-ms Of Proteins In Food Analysiscontrasting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, it was also observed, that neither the electrophoretic behavior nor peak intensity of this protein changed using middle to low temperatures from 25 to 807C, the latter corresponding to the maximum temperature typically used for pasteurization. Although it has been shown that the dissolution pH has some effect on the thermal denaturation of egg-white proteins [71], our results indicate that the procedure based on CE-MS can be less influenced by thermal degradation than those procedures based on antigen-antibody reactions [69,70,72]. Moreover, although the sensitivity provided by immunodiagnostic techniques is in general better than those one obtained by CE-MS, some other aspects, like the longer analysis times usually required for these immunotests (typically hours for ELISA vs. 30 min for CE-MS) and the risk of obtaining false positives due to cross reactions, have also to be kept in mind.…”
Section: Ce-ms Of Proteins In Food Analysiscontrasting
confidence: 68%
“…Since the publications about thermal stability of lysozyme do not agree [69,70], the behavior in CE-MS of this protein after different thermal treatments was analyzed.…”
Section: Ce-ms Of Proteins In Food Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, for processed, minced foie gras products, where anatomical features are lost, the accurate identification becomes progressively more difficult, and opportunities for substitution increase, especially when the products are heated and mixed with spices and other ingredients. Protein-based analytical methods for differentiation of goose and mule duck foie gras are scarce and limited to polyacrylamide disc-gel electrophoresis () and immunological methods ( , ). The main limitation of electrophoretic methods is that the protein profile of a single species produces a complex banding pattern, and even small amounts of protein from other species will often overlap the species-specific bands, making interpretation of the resulting profile equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological atributes and sensory differences are commonly used for species identification, although these criteria may lack reliability when products are processed, heated, and mixed with spices and other ingredients (3,4). Protein-based analytical methods for differentiation of goose and mule duck foie gras are scarce, and are limited to polyacrylamide disc-gel electrophoresis (5) and immunological methods (6,7). However, their reliability might be compromised in heat-treated products, because severe heat treatments denaturate the soluble proteins and may destroy or alter the species-specific epitopes recognized by the antibodies (8).…”
Section: Introductionmentioning
confidence: 99%